Appraising EFL Students’ Syntactic Competency of Word Formation in Argumentative Writing - Kharisma Puspita Sari (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
EFL teaching participants must learn the uncommon language, so that teachers or educators need to discover several problems in conveying the material. This research investigated syntactic labels in recognizing word formation in simple sentences such as subject, verb/predicate, object, and adverb. In previous times, two researchers have investigated EFL students’ capability in identifying parts of speech (noun, adverb, and adjective) and the use of punctuation (comma, full stop, and exclamation mark). Current research aims to fill this gap. This study probes EFL students' propensity to determine syntactic parts of word formation in simple sentences within argumentative texts. This research is applying questionnaires distributed to 51 learning participants. The findings explain that 75% of pupils precisely labeled subjects, verbs, objects, and adverbs. However, challenges remain in differentiating between subjects and objects, as only 25% achieved perfect accuracy. The study concludes that while a larger number of students signified a detailed understanding of syntactic labeling, planned and further interventions are necessary to address continuing obstacles. Hoping that this study could be significant in uncovering the latest techniques in EFL teaching and learning activities, such as the discovery of any media for conveying material on basic syntax for beginner students.